Improved generation of periodic optical trap arrays using noniterative algorithm - Dalal, Anita; Chowdhury, Aniket; Dasgupta, Raktim; Majumder, Shovan Kumar (Optical engineering, 2017)
In a holographic optical tweezers setup, although the use of noniterative algorithms can result in the fast generation of multiple traps array, the performance of these algorithms is often inferior compared to iterative types of algorithms. Particularly in the case of symmetric trap arrays, the performance of noniterative algorithms is very poor. Suitability of the use of a noniterative superposition algorithm for generating symmetric trap arrays has been investigated after introducing small position disorders for the individual traps. It could be seen that the introduction of small disorders in the positions of the individual traps can significantly improve the quality of the generated trap array pattern over the case when an ideal symmetric pattern is targeted.